Comparative Study Between Analytical and Holistic Students' Styles In Artistic Gymnastic Class In College of Physical Education and Sport Sciences Students - Subhi, Ali; Jwad, Heba (Journal of Physical Education, 2017)
The researchers aimed at finding statistical differences between analytical and holistic styles in students during gymnastics class. The researchers used the descriptive method. The subjects were (200) female and male students of the college of physical education and sport sciences/ university of Baghdad academic year 2016 – 2017. The researchers concluded that most of college of physical education and sport sciences' students was Analytical. They also concluded that cognitive styles are effective ways in which individual differences among learners can be revealed. In light of the findings of the researcher recommend taking into account the manner in which students are given practical and theoretical lessons, especially at the Faculty of Physical Education and Sports Sciences/Baghdad University at the Technical College. In addition to that the researcher recommended teaching groups in accordance with the style of the individual in class for students at the Faculty of Physical Education and Sports Sciences/Baghdad University at the Technical College